Effect of Ibandronate Therapy on Serum Chemerin, Vaspin, Omentin-1 and Osteoprotegerin (OPG) in Postmenopausal Osteoporotic Females - Tariq, Saba; Tariq, Sundus; Abualhamael, Shahad Abduljalil; Shahzad, Muhammad (Frontiers in Pharmacology, 2022)
Osteoporosis is a condition in which bone mineral density is reduced due to altered bone microstructure, which results in increased skeletal fragility and incidence of various types of fractures. Adipokines such as chemerin, vaspin, omentin-1 and osteoprotegerin are involved in bone remodeling. The current study was designed to determine the changes in circulating chemerin, vaspin, omentin-1, and osteoprotegerin levels after treatment with oral ibandronate 150 mg in postmenopausal osteoporotic females. The present study enrolled 107 postmenopausal osteoporotic females from a tertiary care hospital in Faisalabad, Pakistan, based on stringent inclusion and exclusion criteria. Sixty-six healthy postmenopausal, non-osteoporotic females with no systemic illness were chosen from the general population. The assessment of bone mineral density (BMD) was done using a DEXA scan. Serum levels of chemerin, vaspin, omentin-1 and osteoprotegerin were estimated using commercially available enzyme-linked immunosorbent assay kits. The collected data were analyzed with the Statistical Package for Social Sciences (SPSS) version 24. Following six months of ibandronate treatment, there was a significant decrease of 24.24% (p<0.033) in serum chemerin levels, as well as a significant increase in serum vaspin levels 343.32% (p<0.001) and osteoprotegerin levels 19.57% (p<0.001), with no significant change in omentin-1 levels. Thus, an increase in serum chemerin levels and a decrease in serum vaspin and osteoprotegerin levels could be implicated in osteoporosis.